Study Profile: The Durban Diabetes Study (DDS): a platform for chronic disease research - Mccarthy, M; Hird, T; Young, E; Pirie, F; Riha, J; Esterhuizen, T; O'Leary, B; Sandhu, M; Motala, A (Cambridge University Press, 2015)
The Durban Diabetes Study (DDS) is a population-based cross-sectional survey of an urban black population in the eThekwini Municipality (city of Durban) in South Africa. The survey combines health, lifestyle and socioeconomic questionnaire data with standardised biophysical measurements, biomarkers for non-communicable and infectious diseases, and genetic data. Data collection for the study is currently underway and the target sample size is 10,000 participants. The DDS has an established infrastructure for survey fieldwork, data collection and management, sample processing and storage, managed data sharing and consent for reapproaching participants, which can be utilised for further research studies. As such, the DDS represents a rich platform for investigating the distribution, interrelation and aetiology of chronic diseases and their risk factors, which is critical for developing health care policies for disease management and prevention.